Balloon to the moon - Mohamad Ismail, Norsazliyana; aharudin, Effa Shadira; Mohd Asmady, Nurfarah Atiqah; Roslee, Amyra Syazwanee; Halim, Nurul Aqilah (2022)
Balloon Rocket Model Experiment was demonstrated to understand the fundamental Physics principle of 2nd law and 3rd law of Motion. This experiment applied a Physics concept involving pressure and thrust force. Different types of load were attached to the filled air balloon before release. The balloon was hung on a horizontal string with a straw used as a stabilizer. It was observed that the greater the load, the more force is needed to accelerate that object. Besides, the increased weight from the cargo slows down the balloon rocket. The results obtained obey the second law and third law of motion and give a clear visualization to enhance students' understanding of both laws.